Porous organic polymers-based fluorescent chemosensors for Fe(III) ions-a functional mimic of siderophores - Mohan, Binduja; Shanmughan, Ananthu; Krishna, Alenthwar Vamshi; Noushija, Mannanthara Kunhumon; Umadevi, Deivasigamani; Shanmugaraju, Sankarasekaran (Frontiers in Chemistry, 2024)
Extended organic polymers such as amorphous Covalent Organic Polymers (COPs) and crystalline Covalent Organic Frameworks (COFs) are emerging functional polymeric materials that have recently been shown promises as luminescent materials for chemosensing applications. A wide variety of luminescence COPs and COFs have been synthesized and successfully used as fluorescence-sensing materials for hazardous environmental pollutants and toxic contaminants. This review exemplifies various COPs and COFs-based fluorescence sensors for selective sensing of Fe(III) ions. The fluorescence sensors are sorted according to their structural features and each section provides a detailed discussion on the synthesis and fluorescence sensing ability of different COPs and COFs towards Fe(III) ions. Also, this review highlights the limitations of the existing organic polymer-based chemosensors and future perspectives on translating COPs and COFs-based fluorescence sensors for the practical detection of Fe(III) ions.